2023
DOI: 10.35534/fibrosis.2023.10002
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Ultraviolet C as a Potential Treatment for COVID-19

Abstract: Currently, low dose radiotherapy (LDRT) is being tested for treating life-threatening pneumonia in COVID-19 patients. Despite the debates over the clinical use of LDRT, some clinical trials have been completed, and most are still ongoing. Ultraviolet C (UVC) irradiation has been proven to be highly efficient in inactivating the coronaviruses, yet is considerably safer than LDRT. This makes UVC an excellent candidate for treating COVID-19 infection, especially in case of severe pneumonia as well as the post COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Reactive oxygen species (ROS) continuously generated by cell metabolism stimulate lipid peroxidation, cause cell membrane damage, and induce alveolar epithelial cell apoptosis 34 . Besides, oxidative stress also causes mitochondrial structural damage by damaging cellular DNA, such as DNA point mutations, DNA breaks, etc 34–36 . Ke et al.…”
Section: Pathological Mechanisms Of Alveolar Epithelium In Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species (ROS) continuously generated by cell metabolism stimulate lipid peroxidation, cause cell membrane damage, and induce alveolar epithelial cell apoptosis 34 . Besides, oxidative stress also causes mitochondrial structural damage by damaging cellular DNA, such as DNA point mutations, DNA breaks, etc 34–36 . Ke et al.…”
Section: Pathological Mechanisms Of Alveolar Epithelium In Lung Injurymentioning
confidence: 99%
“…34 Besides, oxidative stress also causes mitochondrial structural damage by damaging cellular DNA, such as DNA point mutations, DNA breaks, etc. [34][35][36] Ke et al studied the damage of particulate matter 2.5 (PM2.5) to rat AT2 cells and found that excessive ROS levels led to a significant increase in malondialdehyde (MDA) and a decrease in antioxidant enzyme superoxide dismutase (SOD) and antioxidant glutathione (GSH), indicating that oxidative stress is induced by PM2.5 exposure. At the same time, lactate dehydrogenase (LDH) levels increase, mitochondrial membrane potential decreases, and caspase-3/9 expression increases, ultimately leading to AT2 cells apoptosis and indicating the relationship between oxidative stress and apoptosis.…”
Section: Oxidative Stressmentioning
confidence: 99%